Performances of KUB Chickens Fed Diets with Different Nutrient Densities and BS4 Enzyme Supplementation - A. P. Sinurat; T. Haryati; A. Herliatika; N. Pratiwi (Faculty of Animal Science, Bogor Agricultural University, 2022)
An experiment was conducted to study the effect of dietary enzyme supplementation (E) on the performance of KUB chickens fed different nutrient densities (ND). Diets with three densities: 70.7 g crude protein/Mcal or high (H), 66.1 g crude protein/Mcal or medium (M), and 59.3 g crude protein/Mcal or low (L), were formulated and supplemented with or without enzyme. Diets were given in four feeding programs, i.e., H-M-L, H-M-M, M-M-L, and M-L-L during the starter (1–28 d), grower (29–56 d), and finisher (57–84 d) periods, respectively. Each treatment was replicated five times. Bodyweight gain (BWG), feed intake, and FCR were measured each period. At the end of the trial, carcass yield and internal organs were measured. Results of the experiment (1–84 d period) showed that the feed intake was significantly affected by ND. Chickens fed the H-M-L diets have the highest feed intake, while the lowest was found in chickens fed M-M-L diets. A significant interaction was found in the FCR. The best FCR was found in chickens fed the H-M-M diets without enzymes, but the best FCR was found on the M-M-L diets with enzymes. Livability, carcass yield, abdominal fat, liver, proventriculus, and gizzard weights were not affected by the treatments. The jejunum sizes of chickens were significantly longer when fed the low-density diet than those fed the higher nutrient density diet. The ileum sizes of chickens were significantly shorter than chickens fed the diet without enzymes. The highest income over feed cost was achieved when chickens were fed the M-M-L diets supplemented with enzymes. It is concluded that the best performance of growing KUB chickens was obtained when fed M-M-L diets supplemented with BS4 enzymes (30 Units of saccharification/kg diet) and when fed H-M-M diets without enzyme supplementation.